Cost of illness for outpatients attending public and private hospitals in Bangladesh. Issue 1 (December 2016) - Pavel, Md; Chakrabarty, Sayan; Gow, Jeff
Abstract Background A central aim of Universal Health Coverage (UHC) is protection for all against the cost of illness. In a low income country like Bangladesh the cost burden of health care in tertiary facilities is likely to be significant for most citizens. This cost of an episode of illness is a relatively unexplored policy issue in Bangladesh. The objective of this study was to estimate an outpatient's total cost of illness as result of treatment in private and public hospitals in Sylhet, Bangladesh. Methods The study used face to face interviews at three hospitals (one public and two private) to elicit cost data from presenting outpatients. Other socio-economic and demographic data was also collected. A sample of 252 outpatients were randomly selected and interviewed. The total cost of outpatients comprises direct medical costs, non-medical costs and the indirect costs of patients and caregivers. Indirect costs comprise travel and waiting times and income losses associated with treatment. Results The costs of illness are significant for many of Bangladesh citizens. The direct costs are relatively minor compared to the large indirect cost burden that illness places on households. These indirect costs are mainly the result of time off work and foregone wages. Private hospital patients have higher average direct costs than public hospital patients. However, average indirect costs are higher for public hospital patients than private hospital patients by a factor of almost two. Total costs of outpatients are higher in public hospitals compared to private hospitals regardless of patient's income, gender, age or illness. Conclusion Overall, public hospital patients, who tend to be the poorest, bear a larger economic burden of illness and treatment than relatively wealthier private hospital patients. The large economic impacts of illness need a public policy response which at a minimum should include a national health insurance scheme as a matter of urgency.